Research on Parallel Execution Techniques for Improving the Expandability of Database Systems - Zhu, Zhongqi (Journal of Computer, Signal, and System Research, 2025)
In today’s era of widespread big data and cloud computing technology, database systems are under tremendous pressure to handle massive amounts of data and complex queries. When traditional independent database systems encounter high concurrency and large-scale data operations, their performance begins to feel inadequate. Parallel execution technology has been developed as a means to improve database performance and scalability. This technology significantly improves the system’s processing capability and response speed by splitting database queries and transaction processing tasks into multiple small tasks for parallel execution. The purpose of this article is to analyze in depth the role of parallel execution technology in enhancing the scalability of database systems, evaluate the current status and challenges of this technology in database applications, and propose improvement strategies for multi-core and multi node architectures. Through in-depth research on the principles and applications of parallel execution technology, the aim is to provide theoretical support and practical suggestions for improving the scalability of database systems.